Awareness among Indian Dental Graduate Students on Medical Emergency Drugs used in Dental Office: A Pilot Study - Majage, Basavakumar; Kumararama, Sindhu S; Mishra, Sunil K; Chowdhary, Ramesh (Journal of Orofacial Research, 2015)
Background: Effective management of an emergency situation in the dental office is ultimately the dentist’s responsibility. Lack of good training and the inability to cope with these medical emergencies can lead to tragic consequences and sometimes legal action. Aims: Dental students have little understanding about medical emergencies, and there is very little in-depth data about the importance they place on this important area, i.e., fundamental to their professional training. A survey of 50 students from a dental college was carried out to evaluate the amount of awareness about the emergency drugs of the dental office. Materials and methods: The survey was conducted for the students of S Nijalingappa Dental College and Hospital, Gulbarga, India, who were undergoing 1-year mandatory internship. The number of students involved in this pilot survey was 50. A questionnaire was designed to obtain relevant information on the list of emergency drugs a dentist is supposed to know. The responses to the questionnaire so obtained were analyzed. Results: The results showed that undergraduate dental students perceive a need for more intensive education in medical emergency drugs as more than 70% of students were not aware of most of the emergency drugs of choice required in situations like hypotension, anaphylactic shock, allergic reaction, etc. Conclusion: The knowledge for the management of medical emergencies was found to be inadequate among the undergraduate students.